Daratumumab-based treatment of monoclonal gammopathy–associated angioedema due to acquired C1-inhibitor deficiency - Remy S. Petersen, MD; Lauré M. Fijen, MD, PhD; Laurens E. Franssen, MD, PhD; Josephine M.I. Vos, MD, PhD; Danny M. Cohn, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Daratumumab-based treatment could control severe, treatment-refractory, life-threatening angioedema due to acquired C1-inhibitor deficiency associated with monoclonal gammopathy.